2012
DOI: 10.1002/jor.22173
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the metatarsophalangeal joint of the lesser toes: A cadaveric study

Abstract: Dorsal instability of the metatarsophalangeal joint (MTPJ) of the lesser toes is an important cause of forefoot pain. Both conservative and surgical treatment options have been proposed. However, the role of each static stabilizing structure has not been elucidated. We hypothesized that isolated sectioning of the plantar plate (PP) would result in greater dorsal translation compared to isolated sectioning of the medial collateral ligaments (MCL) or lateral (LCL) collateral ligaments, or the extensor hood (EH),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 16 publications
1
33
0
1
Order By: Relevance
“…Bhatia et al [16] and Suero et al [5] used vertical forces measuring vertical translation. Cooper et al [6] used horizontal measurement of total distraction of the metatarsal head and proximal phalanx base.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bhatia et al [16] and Suero et al [5] used vertical forces measuring vertical translation. Cooper et al [6] used horizontal measurement of total distraction of the metatarsal head and proximal phalanx base.…”
Section: Resultsmentioning
confidence: 99%
“…Metatarsalgia symptoms such as gradual onset of forefoot pain, edema and a positive drawer sign can be explained by instability of the metatarsophalangeal (MTP) joint [4, 5], MTP joint instability is described as a dorsal subluxation or dislocation of the base of the proximal phalanx over the metatarsal head. The traditional etiology of instability of the lesser MTP joints in the sagittal and/or transverse plane is described in the literature by plantar plate degeneration and rupture [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is known that the plantar plate plays an important role in the stabilization of the lesser metatarsophalangeal joints. Recent biomechanical studies have shown that PP was the main isolated stabilizer of the MTP joints in the dorsal–plantar direction [ 4 ]. Deland and Sung [ 20 ] showed how an isolated repair of the collateral ligaments was insufficient to resolve instability resulting from PP deformity, which may indicate that the PP itself has a crucial role in stabilizing the joint.…”
Section: Discussionmentioning
confidence: 99%
“…The MTP joint is primarily stabilized by the plantar plate, 12,21,40 and damage through repetitive stress ultimately leads to an unstable joint. 6,21,34 The plantar plate is a critical anatomic structure composed of fibrocartilage that lies on the inferior aspect of the MTP joint (Figure 1). 12,14 Without its support, the proximal phalanx will deviate dorsally.…”
Section: Etiology Of Lesser Mtp Instabilitymentioning
confidence: 99%